Revolutions of multiferroic materials - Pu Yu (npj Spintronics)
Multiferroic materials, which simultaneously exhibit ferroelectric and magnetic orders, provide a unique platform to explore the interplay between charge and spin degrees of freedom for spintronics applications. These materials enable novel functionalities and applications, making them a focal point of research in condensed matter physics and materials science. This Editorial highlights current stage of multiferroic research and discusses future directions in this rapidly evolving field.